Gender Earnings Gaps in the World - Ñopo, Hugo; Daza, Nancy; Ramos, Johanna (Washington, DC: World Bank, 2012)
This paper documents gender disparities in labor earnings for sixty-four countries around the world. Disparities are partially attributed to gender differences in observable socio-demographic and job characteristics. These characteristics are used to match males and females such that gender earnings disparities are computed only among individuals with the same characteristics, as in Ñopo (2008). After comparing males and females with the same characteristics we found that the earnings gap falls on a range between 8% and 48% of average females' earnings, being more pronounced in South Asia and Sub-Saharan Africa. The unexplained earnings gaps are more pronounced among part-time workers and those with low education.